The effect of light variations by photoselective shade nets on pigments, antioxidant capacity, and growth of two ornamental plant species: Marigold (Calendula officinalis L.) and violet (Viola tricolor) - Seyedeh Khadijeh Abbasnia Zare; Shahram Sedaghathoor; Mohammad-Naghi Padasht Dahkaei; Davood Hashemabadi (Cogent Food & Agriculture, 2019)
A new group of colored shade net has been developed that can influence the quality and quantity of the light intercepted by the plants. To explore the effect of applying colored shade nets on physiological traits of marigold and violet plants, a split-plot experiment was carried out. The trial was done with two factors including colored shade net at four levels (no net, green, yellow and red net) and two plant species (marigold and violet). The results showed that yellow shade net increased the vegetative growth of the plants. However, the highest leaf area was related to the red shade net. Chlorophyll content, Brix°, and carotenoid content were significantly higher in plants grown under the yellow net. The highest peroxidase was obtained from green and red shade nets. The plants grown under the green shade net had higher anthocyanin and antioxidant activities than other shade nets. The interaction of “shade net × plant species” showed that the highest root and flower fresh weights were related to “yellow net × marigold”, the highest plant growth rate, total chlorophyll, and carotenoid contents was related to “yellow net × violet”. The results revealed that yellow shade nets outperformed the other nets in improving plant growth.